Chapter Il “Cesare Alfieri” dalla fondazione al 1938 - MANICA, GIUSTINA (Firenze University Press, 2025)
On May the 5th, 1875, Marquis Carlo Alfieri di Sostegno announced the foundation of the School of Social Sciences. In 1877, the School settled permanently in the former convent of Crocette, in via Laura 42. The first years of the School were characterized by relevant financial difficulties, but also by countless successes. Between 1887 and 1909, the number of students enrolled increased from 43 to 87. The number of courses gradually rose from 8 to 19. By March 1909, the Royal Institute had already graduated up to 245 students. During the Italian participation to the World War, the Institute was stressed by the drop in registrations caused. Although at the eve of the fascist seizure of power and of the high education reform launched by Giovanni Gentile, the "Cesare Alfieri" Institute represented a great reality.